Sustainable Development MINE-UNIVERSITY-COMMUNITY - Cardenas Serrano, Christofer (2018)
The mining sector in Peru is the most influential industry in the development of our economy, contributes 20% of fiscal revenues, contributes around 14% national GDP and 62% of exports. Mining activity produces prosperity in the areas where it is carried out, but undoubtedly generates an environmental impact like any other activity. In recent years, mining megaprojects have been paralyzed by the social conflict between companies and communities, who oppose the implementation of these basing their arguments on the pollution generated by this sector. Unaware that all development goes hand in hand with pollution, but it is the responsibility of the companies themselves to minimize them. Working with communities is an essential and complex issue in the development of mining activity, it is a challenge to which we have to adapt and propose possible scenarios that lead to the development of mining projects with social responsibility and safety. Today, we can observe that industrialized countries such as Australia, Canada or the United States make possible the coexistence of mining and agriculture. The question we ask ourselves: What is missing from us to make this coexistence possible?